Implementasi Model Project Based Learning dalam Pembelajaran Sejarah Kebudayaan Islam - Amalia, Dwi Prasiska; Nugroho, Ischak Suryo (Asian Journal of Islamic Studies and Da'wah, 2025)
Low student interest in the subject of Sejarah Kebudayaan Islam (Islamic Cultural History) is often attributed to the use of conventional teaching approaches that are passive and monotonous. This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in SKI instruction, evaluate its effectiveness, and identify the supporting and inhibiting factors influencing its execution. A qualitative case study design was employed, involving 30 tenth-grade students at Madrasah Aliyah Assalam Bantarkawung. Data were collected through observations, interviews, and documentation of learning activities designed around group work, paper writing, and the creation of creative media such as family trees and pop-up books. The findings indicate that the application of PjBL enhances student enthusiasm, active participation, and creativity, with a success rate of 80%. These results align with constructivist theory, which emphasizes meaningful learning through direct experience and active learner engagement. This study contributes theoretically to the development of project-based instructional models within Islamic religious education and offers practical implications for educators and institutions in designing contextual, collaborative, and 21st-century competency-oriented learning.